2022
DOI: 10.1038/s41598-022-12015-9
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness of testing, vaccinations and contact restrictions for containing the CoViD-19 pandemic

Abstract: In order to slow the spread of the CoViD-19 pandemic, governments around the world have enacted a wide set of policies limiting the transmission of the disease. Initially, these focused on non-pharmaceutical interventions; more recently, vaccinations and large-scale rapid testing have started to play a major role. The objective of this study is to explain the quantitative effects of these policies on determining the course of the pandemic, allowing for factors like seasonality or virus strains with different t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 31 publications
1
6
0
Order By: Relevance
“…Finally, the results showed that seasonality may have an effect in slowing the spread of infections. Incidence was substantially lower in the summer compared to the winter months in Neukölln, which is in line with previous research that found that infectiousness increased during winter, owing to more frequent indoor gatherings and weakened immune systems ( 10 , 11 , 71 ).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Finally, the results showed that seasonality may have an effect in slowing the spread of infections. Incidence was substantially lower in the summer compared to the winter months in Neukölln, which is in line with previous research that found that infectiousness increased during winter, owing to more frequent indoor gatherings and weakened immune systems ( 10 , 11 , 71 ).…”
Section: Discussionsupporting
confidence: 91%
“…The impact of testing on the occurrence of cases has also been shown in other regions and in other pandemic phases ( 14 , 70 ). Still, frequent and large-scale rapid testing was evidently an effective means of decreasing case numbers in Germany during the third pandemic wave ( 71 ). The introduction of rapid antigen tests has made it possible to identify cases that would otherwise remain undetected and to isolate infected individuals in time before the infection was passed on to others.…”
Section: Discussionmentioning
confidence: 99%
“…With the COVID‐19 pandemic accelerating, provisions for remote work have also been used to protect employees from being infected at the workplace. By way of avoiding potentially hazardous commutes as well as crowded office spaces, providing employees with remote work options has served as one of the most powerful weapons for protecting employees during the pandemic (Gabler et al, 2021; Neumann et al, 2020). In our estimate, the dependent variable takes the value of “1” when there are provisions available at the establishment level which allow employees to take advantage of remote work/home office arrangements.…”
Section: Variables and Resultsmentioning
confidence: 99%
“…The copyright holder for this preprint this version posted September 9, 2022. ; https://doi.org/10.1101/2022.09.05.22279618 doi: medRxiv preprint leading to increased number of contagions and further spread of the disease [34].…”
Section: Covid-19 Testing Technologiesmentioning
confidence: 99%
“…Mass testing using RT-qPCR for the entire population is infeasible for most countries. Moreover, increased testing volumes can rapidly saturate a limited number of analysis facilities, September 5, 2022 3/37 leading to increased number of contagions and further spread of the disease [34].…”
Section: Covid-19 Testing Technologiesmentioning
confidence: 99%